2018
DOI: 10.1080/08869634.2017.1414347
|View full text |Cite
|
Sign up to set email alerts
|

The role of occlusion in temporomandibular disorders (TMD) in the Northern Finland Birth Cohort (NFBC) 1966

Abstract: Objective To investigate the role of occlusion in temporomandibular disorders (TMDs) in the Northern Finland Birth Cohort 1966 (NFBC 1966). Methods Subjects (n = 1962) participated in clinical medical and dental examinations. The association between TMD signs and diagnoses with occlusal disturbances, i.e. malocclusions and occlusal interferences, was examined. Pearson's chi-square test, as expressed by odds ratios (OR) and 95% confidence intervals (CI) and logistic regression models, were used in the analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In other words, the present work relates the acute dental malocclusion through UAC to multiple neuromuscular activity. It has been reported that TMD has a close relationship with occlusion . Patients with TMD often have widespread palpation tenderness in cervical and other body muscles, in addition to painful masticatory muscles .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the present work relates the acute dental malocclusion through UAC to multiple neuromuscular activity. It has been reported that TMD has a close relationship with occlusion . Patients with TMD often have widespread palpation tenderness in cervical and other body muscles, in addition to painful masticatory muscles .…”
Section: Discussionmentioning
confidence: 99%
“…53 The literature also illustrates how such transverse occlusal discrepancies would impact muscular condition and function. Jussila et al 54 demonstrated association between myalgia and lateral scissor bite.…”
Section: Discussionmentioning
confidence: 99%
“…The features occurring more frequently in patients with temporomandibular disease than healthy individuals can be pronounced overjet, skeletal anterior open-bite, early contact or lateral deviation during jaw closure, loss of molar support and trabecular structure changes in the joint area bones. Occlusal condition may cause temporomandibular disorder symptoms by affecting mandibular functions as a result of mandible instability and acute changes in occlusal relationships 17 . Relationships between teeth and malocclusions have been found to be associated with temporomandibular disorders 12 .…”
Section: Discussionmentioning
confidence: 99%